2006
DOI: 10.1002/pssc.200562727
|View full text |Cite
|
Sign up to set email alerts
|

Spreading resistance microscopy study of polyamidine thin films

Abstract: We have observed that thin films of polyamidine may exhibit high conductivity in some locations on the polymer surface at low electrical field strength. The conductance which has been tested by spreading resistance mode of an atomic force microscope depended on the type of substrate. We consider that a critical density of charge inside the polymer is needed for its switching to the conductive state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Whereas doped polymers have conductivity levels similar to semiconductors. It is shown that films of such materials have metallic type conductivity [8][9][10][11][12][13][14]. Considering chemical structure of the polymers, conductivity of such polymer films can be selectively altered.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas doped polymers have conductivity levels similar to semiconductors. It is shown that films of such materials have metallic type conductivity [8][9][10][11][12][13][14]. Considering chemical structure of the polymers, conductivity of such polymer films can be selectively altered.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is true only for thick bulk polymers. In thin films of different materials, high conductivity was found in small (quasi-one-dimen-sional) conducting channels [2,3]. This has been reported in polypropylene [4][5][6], polyimide [7], imidesiloxane co-polymer [8], poly(3,3`-phthalidylidene-4,4`biphenylene) [9,10], poly-(diethyl)siloxane [11], and polyamidine [3].…”
mentioning
confidence: 77%
“…In thin films of different materials, high conductivity was found in small (quasi-one-dimen-sional) conducting channels [2,3]. This has been reported in polypropylene [4][5][6], polyimide [7], imidesiloxane co-polymer [8], poly(3,3`-phthalidylidene-4,4`biphenylene) [9,10], poly-(diethyl)siloxane [11], and polyamidine [3]. Figure 1 shows the currentvoltage characteristics at different locations on a polyamidine thin film, which we obtained by scanning the surface with an atomic force microscope in the spreading resistance mode at room temperature.…”
mentioning
confidence: 99%
“…For example, for almost all polymer insulators a sliding contact is much more effective for the electrification than a permanently touching one. Figure 4 Dependence of the current value versus the number (n) of CVC measurement cycles, which were done by an AFM (E = 3 x 10 3 V/cm, R tip ≈ 30 nm) at a point corresponding to dark regions of the polymer surface, see [9], Fig. 2a.…”
Section: Contributed Articlementioning
confidence: 99%
“…There are two mechanisms which can explain this effect: i) The first mechanism requires the insulator to be slightly conducting, so that when the contact is removed charge flows away from the contact region into the bulk of the insulator up to several microns [5]; ii) The second mechanism supposes that the second touch is realised at a slightly different place on the polymer surface, so that the total amount of accumulated charge continuously increases. In order to check the influence of charge accumulation on the appearance of metallic conductivity, the following experiment was performed [9]. At a location on the polymer surface without Ohmic behaviour a voltage, U ≤ 300 mV, was applied, which was much less than the voltage for a reversible switching (Fig.…”
Section: Contributed Articlementioning
confidence: 99%